Pain freedom after 2 hours should be the primary outcome in controlled trials treating migraine attacks. (October 2020) - Tfelt-Hansen, Peer; Diener, Hans-Christoph
Background: Pain freedom after 2 hours is the recommended primary endpoint by the International Headache Society in randomized trials investigating drug treatment of acute migraine attacks. In order to demonstrate an early effect of a drug, some drug companies, however, have promoted headache relief (improvement from severe or moderate pain to mild or no pain) at earlier time points than 2 hours as outcome parameter. Methods and results: We analyzed the relationship between pain freedom and headache relief in acute migraine trials and observed that persistent mild headache constituted 90% of headache relief after 0.5 hour and 40% of headache relief after 2 hours. Conclusion: Headache relief at 2 hours should in our view only be used as an outcome measure for comparison with historic data. Prior to 2 hours, headache relief varies with time from intake and the therapeutic gain is very small. Therefore, pain freedom should be used at these early time points.